English translation of traditional Chinese architectural terms: systematic analysis based on international journal papers - Ding Ding; Yaqing Yu; Qi Tang (Journal of Asian Architecture and Building Engineering)
Terminology translation plays a crucial role in promoting the integration of world cultures; however, the English translation of traditional Chinese architectural terms poses significant challenges due to their inherent characteristics such as confusion and temporal and spatial variations. By searching international journals indexed by Web of Science, 2740 papers related to Chinese traditional architecture published after 2002 have been obtained. Out of these publications, 455 papers were selected for quantitative analysis. Through text selection and reference to Chinese and English bilingual books and core journal papers published in China, this work extracted the English translation of terms recognized by Chinese and foreign scholars and summarized their types and translation methods. From the professional perspective of architecture, several groups of typical terms related to beams and columns, roofs, timber structures, bracket sets, and siheyuan were taken as examples and combined with pictures to intuitively show the meaning of the terms.